Rosacea is associated with conjoined interactions between physical barrier of the skin and microorganisms: A pilot study. Issue 9 (17th May 2020) - Yuan, Chao; Ma, Yafeng; Wang, Yinjuan; Wang, Xiuli; Qian, Chunyan; Hocquet, Didier; Zheng, Shuli; Mac‐Mary, Sophie; Humbert, Philippe
Abstract: Background: Rosacea is a common condition characterized by transient or persistent central facial erythema, and often papules and pustules. Currently, the role of bacterium in the development and progression of rosacea remains controversial. This study aimed to investigate the difference in the physiological conditions and microorganisms between the lesional and non‐lesional areas of papulopustular rosacea. Methods: Twenty‐five French patients with papulopustular rosacea were enrolled in this pilot study. Each patient was subjected to clinical assessment, and the skin barrier function was tested in lesional and non‐lesional areas. In addition, samples from the lesional and non‐lesional areas were collected for bacterial culturing. Results: Of all subjects included in the study, a lower skin conductivity was measured in lesional areas than in non‐lesional areas (43.5 ± 12.4 vs. 57.2 ± 11.6 U, P  < .05), and a higher transepidermal water loss (TEWL) value was found in lesional areas than in non‐lesional areas (17.2 ± 5.9 vs. 14.2 ± 4.1 g/(m 2  h), P  < .05). We found a lower TEWL in lesions in rosacea patients with bacterial dysbiosis than in those with bacterial balance ( P  < .05). In addition, there were significant differences in the skin conductivity and TEWL between lesional and non‐lesional areas in patients with bacterial dysbiosis ( P  < .001), and no significant differences were seen in patients with bacterial balance ( P  < .05). Conclusion: The results of the present study demonstrate that the physiological features of rosacea are closely associated with the interactions between the host and the microorganisms.